El desarrollo socioemocional y la regulación en la conducta de los niños de Educación Inicial II - Caiza Tamaquiza, Tatiana Abigail (2024)
Socio-emotional development and behavioral regulation constitute central benefits during early childhood, contributing to the achievement of healthy bonds, social integration, school achievement and subsequent mental health, for this reason the present research aims to “Diagnose the socio-emotional development and the regulation of behavior in the boys and girls of the sub-initial II of the “Semillitas” Cesar Francisco Naranjo Rumazo Initial Education Center in the 2023-2024 school year, a mixed approach was used to carry out the research project with a non-experimental research design, the inductive and deductive method guided the research process, from a bibliographic and field research. The observation technique applied to 18 infants was used. As well as, the technique of the survey which was addressed to 18 parents and the interview was applied for the teacher of the institution. The results of the triangulation are: the teacher has a clear concept of the importance of the socioemotional area in the development of children, but unfortunately there is a lack of knowledge of innovative strategies to develop the socioemotional area with the behavior of children in early education; Similarly, from the perspective of parents, 85% claim to know about socioemotional development, while 15% do not know about it. Finally, the observation allowed detecting that 16.67% of the infants understand the emotional state of their children, 83.33% do not understand it, which implies ignorance of their emotions and those of their classmates. In conclusion, children have difficulties in achieving adequate social interaction for the learning process both at school and in the family environment.